Theoretical Critique in Iranian Theater - Farshid Ebrahimian, Kaveh Oveisi; Sojoudi, Farzan (Opción, 2019)
In this research, we are trying to review the critique history of the theatre and views of experts and their conclusion to investigate it in contemporary history of Iran. This research is based on the library method and the adaptations are gathered in various journals and books about their summary and investigation. In result, artistic and the first dramatic critique are also addressed to an audience, and can never be a critic of the internal dialogue. In conclusion, the critic must be trained as a philosopher and academically and scientifically learn criticism at the university.